2010
DOI: 10.1074/jbc.m110.127829
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Human Apolipoprotein A-I Preserves Cognitive Function and Attenuates Neuroinflammation and Cerebral Amyloid Angiopathy in a Mouse Model of Alzheimer Disease

Abstract: To date there is no effective therapy for Alzheimer disease (AD). High levels of circulating high density lipoprotein (HDL) and its main protein, apolipoprotein A-I (apoA-I), reduce the risk of cardiovascular disease. Clinical studies show that plasma HDL cholesterol and apoA-I levels are low in patients with AD. To investigate if increasing plasma apoA-I/HDL levels ameliorates AD-like memory deficits and amyloid-␤ (A␤) deposition, we generated a line of triple transgenic (Tg) mice overexpressing mutant forms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
170
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(178 citation statements)
references
References 67 publications
5
170
3
Order By: Relevance
“…51) Recent studies with genetic modifications of apo AI in AD mouse models demonstrate that apo AI performs protective roles in memory and AD pathology. 92,93) Furthermore, a remarkable reduction of apo AI has been shown in the CSF and brain of schizophrenia patients. 94) Thus, apo AI incorporated into the brain from the circulation might play important roles in the CNS.…”
Section: Lipoproteins In the Cnsmentioning
confidence: 99%
See 1 more Smart Citation
“…51) Recent studies with genetic modifications of apo AI in AD mouse models demonstrate that apo AI performs protective roles in memory and AD pathology. 92,93) Furthermore, a remarkable reduction of apo AI has been shown in the CSF and brain of schizophrenia patients. 94) Thus, apo AI incorporated into the brain from the circulation might play important roles in the CNS.…”
Section: Lipoproteins In the Cnsmentioning
confidence: 99%
“…162) However, it was recently reported that over-expression of human apo AI preserves cognitive function and attenuates neuroinflammation and cerebral amyloid angiopathy in a mouse model of AD. 92) In addition, a deficiency of apo AI in AD model mice (APPSwe/PS1DE9) accelerated the memory deficits and caused significant cerebral amyloid angiopathy. 93) Variation in the apo AI gene might also influence the age of onset and the risk of AD.…”
Section: Lipid Metabolism and Admentioning
confidence: 99%
“…Crossing of ApoA1 null mice with AD model mice resulted no change in amyloid deposition in the brain (Fagan et al 2004). Similarly, when ApoA1 overexpressing mice were crossed with AD model mice, no alteration in amyloid metabolism was observed (Lewis et al 2010). Our result presented here shows that expression of ApoA1 was downregulated in Hsp27 transgenic mice, indicating that Hsp27 might have a role in the regulation (directly or indirectly) of ApoA1 expression.…”
Section: Discussionsupporting
confidence: 55%
“…1 and Table 1, the effects of cross-amyloid interactions between different amyloid proteins may vary substantially. TTR (59), CysC (67), and apoA-I (62) all suppress A␤ fibrillation and delay AD progression in mice (57,64). In contrast, ␣-syn (23), tau (28), and fibrinogen-␣ (95) promote A␤ toxicity and/or fibrillation and increase the risk of AD in mice (32) and/or patients (25,76).…”
Section: Implications Of A␤ Cross-amyloid Interactionsmentioning
confidence: 99%
“…Polymorphisms of the promoter region of apoA-I are associated with increased AD risk (63). In an AD mouse model, overexpression of apoA-I impaired learning and caused memory deficits (64).…”
Section: Apolipoprotein Aimentioning
confidence: 99%